(untitled) (Semiárida, 2023)
The First Pampean Meeting on Lentic Ecosystems and the Conservation of their Biodiversity took place on March 30 and 31, 2023 in the Benicio Delfín Pérez Urban Natural Reserve, located in General Pico, La Pampa. This meeting was conceived as a place for the exchange of experiences related to the knowledge and conservation of the biodiversity of lentic ecosystems, with particular emphasis on urban natural reserves. The event was organized by the National University of La Pampa, the Municipality of General Pico and the Natural Sciences Professional Council of La Pampa. The program included conferences related to water resources and the protected areas of La Pampa, the characterization of the Benicio Delfín Pérez Urban Natural Reserve and its role as a recreational and environmental education space, and the use of bioindicators and contributions from Citizen Science to monitoring aquatic ecosystems and their environment. Additionally, three round tables were carried out on topics related to flora, bioaquatic resources and fauna, and there were presentations of digital poster in topics ranging from education to extension, and biological and environmental sciences. These meeting served as a starting point for the proposal of research projects, management strategies and tools aimed at recovering, conserving and protecting the ecosystems of the Benicio Delfín Pérez Urban Natural Reserve.